Efektivitas Media Pembelajaran Daring melalui Google Classroom - Muhammad Arifin Rahmanto; Bunyamin Bunyamin (Jurnal Pendidikan Islam, 2020)
The demands of the times and government policies to break the chain of COVID-19, namely using learning carried out online, causing teachers and lecturers to be obliged to take advantage of digital-based technology, one of which is Google classroom. The use of the Google classroom application has several weaknesses, such as being accessible only by a google account and the absence of notification that the material presented has been fully read by students so that the effectiveness of Google classroom is still in doubt. The purpose of this research is to determine the effectiveness of online learning through Google classroom in the educational administration practicum course. This study uses a qualitative method. This research data collection method through interviews to produce primary data. The result of this research is that Google classroom is effectively used in the educational administration practicum subject because students and lecturers can easily access it according to the needs of the lecture. The effectiveness of the Educational Administration Practicum Lecture can be seen from the student learning outcomes which are increasing every day through assignments and quizzes.